2013
DOI: 10.1007/s10103-013-1295-4
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic inactivation of Candida albicans mediated by a low density of light energy

Abstract: Shorter times and lower energies of application of light sources are desirable to use photodynamic antimicrobial chemotherapy (PACT) to the clinical control of candidiasis, especially among babies and children. Light energies ranging from 39.5 to 100 J/cm(2) were previously applied to kill Candida albicans by PACT. The present study evaluated the efficacy of a combination of 0.05 mg/mL toluidine blue O (TBO) and a short time of application (60 s) and a low density of light energy (18 J/cm(2)) of a red light-em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Other incubation times used in that study were 1 min [46,47], 10 min [48] and 20 min [29]. In two other studies of TBO-mediated aPDT, the applied PIT was not reported [49,50]. All these studies showed the efficacy of the therapy as a reduction in the number of cells or % CFU/mL, but only that by Nielsen et al showed complete elimination of C. albicans from the planktonic solution (LED 635 nm, 37.7 J/cm 2 , 400 mW, TBO concentration 0.226 mM, PIT 1 min) [47] and the others showed only a partial reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Other incubation times used in that study were 1 min [46,47], 10 min [48] and 20 min [29]. In two other studies of TBO-mediated aPDT, the applied PIT was not reported [49,50]. All these studies showed the efficacy of the therapy as a reduction in the number of cells or % CFU/mL, but only that by Nielsen et al showed complete elimination of C. albicans from the planktonic solution (LED 635 nm, 37.7 J/cm 2 , 400 mW, TBO concentration 0.226 mM, PIT 1 min) [47] and the others showed only a partial reduction.…”
Section: Discussionmentioning
confidence: 99%
“…This equation was also satisfied in analysis of the growth of the fungus Aspergillus nidulans [29]. The growth of C. albicans may have been inhibited by the photoinactivation phenomenon [30], altering the exponents of scale. Therefore, the variation in the growth rate must be considered as a factor of modification in the pattern of microorganism development.…”
Section: Growth Dynamicsmentioning
confidence: 99%
“…18,19 Barbario et al recently demonstrated a significant kill rate of C. albicans when exposed to a combination of 0.05 mg/mL toluidine blue O and 18 J/cm 2 of red light. 20 In an in vivo study, Dai et al found UVC light (254 nm) to be superior to a topical antifungal drug in treating C. albicans. 5 Based on these results, it can be said that C. albicans can be treated with various wavelengths when appropriate photosensitizers are included.…”
Section: Introductionmentioning
confidence: 99%